The Determinant of Environmental Disclosure in ASEAN Countries - Indah Fajarini Sri Wahyuningrum; Lisdiana Safitri; Shanty Oktavilia; Andryan Setyadharma (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The purpose of this study is to examine the effect of firm size, industry type, profitability, firm age, environmental performance, institutional ownership, and gender diversity on environmental disclosure. The quantity of environmental disclosure is measured using disclosure scoring by giving “1” for items disclosed and “0” for items that are not disclosed. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) and Kuala Lumpur, Stock. Exchange (KLSE) in the year 2019. The sampling technique used was purposive sampling which resulted in 74 companies. The analytical technique used in this research is multiple linear regression analysis using IBM SPSS Statistics version 25. The results of this study indicate that company size, company age, and environmental performance have a significant positive effect on environmental disclosure. The type of industry, profitability, institutional ownership, and gender diversity does not affect environmental disclosure. Based on the study results, it can be concluded that companies that are large in size and mature in age and equipped with ownership of ISO 14001 certification can contribute to making more comprehensive environmental disclosures.